How does sprawl differ across urban built-up land types in China? A spatial-temporal analysis of the Beijing metropolitan area using granted land parcel data. (October 2016) - Jiang, Guanghui; Ma, Wenqiu; Qu, Yanbo; Zhang, Ruijuan; Zhou, Dingyang
Abstract: The inner structure of urban built-up land sprawl (UBLS) is crucial for the level and quality of urbanization. This paper attempts an in-depth analysis of the inner structure of UBLS based on site data of granted built-up land parcels within the Beijing Metropolitan Area from 2001 to 2012. Structure entropy analysis and kernel density estimation (KDE) are employed to characterize the spatial-temporal variation of different types of UBLS and to summarize their patterns. The results reveal that during the sprawl process, residential land expanded rapidly in the first half of the study period while industrial land expanded rapidly in the second half. Residential land sprawl illustrated "radial sprawl", with a trend of "living suburbanization"; commercial land tended to follow the pattern of "ribbon sprawl along the main roads"; and industrial land sprawl was scattered in a "leapfrog sprawl" pattern. These results reveal the particular characteristics of the coexistence of market mechanisms and government macro-control of the land market in China. The land analysed in this study does not present the high-efficiency circle-layer land-use structure. Driven by top-down power allocations and the GDP-dominated views of local governments, the land supply inclined toward structural imbalance, which generated a disordered urban spatial structure. Hence, we suggest formulating a market-driven land supply mechanism to adjust the land-use supply structure, which has important implications for optimizing urban land-use structure. Highlights: Explore the inner structure of urban built-up land sprawl(UBLS). UBLS in China is influenced by the coexistence of market mechanisms and government macro-control. Characterize the spatial–temporal variation of different types of UBLS.